JURIDICAL OVERVIEW OF MEDICAL TELECONSULTATION PRACTICE DURING THE COVID-19 PANDEMIC: A NARRATIVE REVIEW - Vera Rimbawani Sushanty (Nurse and Health: Jurnal Keperawatan, 2022)
The mandate of the 1945 Constitution, that everyone has the right to live in physical and spiritual prosperity, to live and to have a good and healthy living environment, and the right to obtain health services while the ratio or comparison of health workers in this case doctors and the population in Indonesia is not balanced or not at the ideal number. In order to equalize the rights of citizens to obtain adequate and standard health services, the government issued a regulation on telemedicine in this case more often referred to as teleconsultation. Especially in this era of the Covid-19 pandemic, these services are very helpful for the community, so that their health conditions are monitored. It is hoped that services using information and communication technology facilities will have a good impact as well as conventional medical services and still pay attention to the rights and responsibilities of both parties and do not cause losses in their implementation, the preparation of this research uses the type of normative research. The materials for this research come from laws and regulations, regulations issued by the Minister of Health, the Civil Code, as well as other relevant sources.